Administrative management and the teaching performance from a language center in Lima Metropolitan - Chumpitazi Medina, Farrath Piera (2020)
This article reflects on the administrative management and teaching performance in a language center in Lima Metropolitan. The dimensions of management become important given the need to define, delimit and conceptualize the areas of competence in the complex social phenomenon of formal education. On the other hand, foreign language teachers have as competence the application of knowledge to respond to the situations they face in their professional activity. This work is prepared thinking that defining and understanding the concepts of administrative management and teacher performance will promote better educational practices for both the institution and the students.